Attitude, knowledge and factors associated with influenza and pneumococcal vaccine uptake in a large cohort of patients with secondary immune deficiency. Issue 31 (17th July 2015) - Loubet, Paul; Kernéis, Solen; Groh, Matthieu; Loulergue, Pierre; Blanche, Philippe; Verger, Pierre; Launay, Odile
Abstract Background Immunocompromised patients are at increased risk for severe influenza and invasive pneumococcal diseases. Population-specific vaccine recommendations are thus warranted. This study aimed to estimate the prevalence and predictors of influenza and pneumococcal vaccine uptake in a large cohort of patients with secondary immune deficiency. Methods An anonymous online survey was submitted to the members of 11 French associations of immunocompromised patients. The questionnaire included questions concerning underlying disease, care and treatment, flu and pneumococcal vaccine uptake, attitudes and knowledge about vaccination. Factors associated with vaccine uptake were assessed by multivariate logistic regression. Results Among the 10, 897 solicited patients, 3653 agreed to participate (33.5%): 75% were female, 20% aged 65+, 79% were followed for an autoimmune disease, 13% were solid organ recipients or waiting for transplantation and 8% were treated for hematological malignancies. 3109 (85%) participants were treated with immunosuppressive therapy. Self-reported vaccine uptake was 59% (95%CI [57–60]) against seasonal influenza and 49% (95%CI [47–50]) against pneumococcal diseases. Better knowledge of and favorable attitudes toward vaccination were positively associated with vaccine uptake while being treated with a biological therapy was negatively associated. Conclusion Despite specific recommendations regarding immunocompromised patients, influenza and pneumococcal vaccination rates do not reach recommended levels. Targeted information campaigns on vaccination toward these populations should be implemented to improve vaccine coverage and thus reduce the burden of infections.